Development of a DNA-based detection method for sewage specific bacteriophages of bacteroides - Aurin Wongpichit; Kwanrawee Sirikanchana; Preeda Pakpian; Rojana Sukchawalit; Chulabhorn Research Institute; Mahidol University; Asian Institute of Technology, Fellowship (Pathum Thani : Asian Institute of Technology, 2012)
Bacteriophages of Bacteroides are one of the new types of fecal indicators that are currently being evaluated in regions outside Asia. Bacteriophage strain ATCC 51477-B1, which infects B. fragilis strain HSP40 (ATCC 51477), has been reported to be found only in water samples contaminated with human-derived fecal materials. On the other hand, the strain ATCC 700786-B1, which infects B. fragilis strain RYC2056 (ATCC 700786), was shown to be detected in fecally contaminated water samples of both human and animal origins. The genomic information of phage ATCC 51477-B1 has been fully characterized. However, that of bacteriophage ATCC 700786-B1 has not yet been studied. Since a non-specific strain (ATCC 700786-B1) was found more prevalently in water, it is important for the newly-designed DNA-based assay not to pick up this non-specific phage strain as well. Therefore, there is a need to develop the detection method that can detect the human-specific bacteriophage strain. There are 2 objectives of this study. The first objective was to determine regions of difference in DNA sequences between bacteriophages strain ATCC 51477-B1, representing a sewage-specific strain, and strain ATCC 700786-B1, representing a non-specific strain. The regions of difference between these two phage strains were determined using molecular techniques such as restriction enzyme digestion, DNA sequencing and sequence analysis. The second objective was to design a PCR assay for detection of human-specific bacteriophage strain ATCC 51477-B1. This objective was performed by PCR primer designing, optimizing the PCR reaction components and cycling conditions, and determining the detection limit of the newly-designed PCR assay. The whole genomic sequencing results was performed with Ion Torrent Personal Genome Machine System. The resulting DNA sequences were assembled and analysed with de novo genome assembly software and Blastn program. Four regions in the length of 400 bps{u2013}1 Kbps of bacteriophage ATCC 51477-B1 that were not in bacteriophage ATCC 700786-B1 were determined: node 43 (440 bp), node 13 (866 bp), node79 (443 bp), and node 9 (941 bp). The 4 pairs of primers were designed from 4 regions of phage ATCC 51477-B1 and the results showed PCR products in the length of 433, 591, 592 and 593 bp. After that, the PCR reaction components and cycling conditions were optimized and the PCR method detection limit was determined. Moreover, the newly-designed PCR method was used with wastewater samples to detect phage ATCC 51477-B1. The results indicated that the amount of phage ATCC 51477-B1 of less than 257 pfu/ml in wastewater samples were not detected. Therefore, after being validated with more environmental samples, the method will be ready for measuring water quality, tracking human-derived fecal sources, and facilitating in water management and pollution control of water sources.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Science in Environmental Engineering and Management Inter - University Program on Environmental Toxicology, Technology and Management
Thesis (M.Sc.) - Asian Institute of Technology - Chulabhorn Research Institute - Mahidol University, 2012
Keywords: Sewage -- Purification; Bacteroides